Scientific writing (Engineering) - Rosmawati, Naim (Penerbit UMP, 2017)

(untitled)
This module provides an overview on how to write a good scientific manuscript. There are 5 main sections outlined in this module which includes Section 1: Importance of Scientific Writing, Section 2: Types of Scientific Writing, Section 3: Content of Good Scientific Manuscript, Section 4: Scientific Style of Language and Section 5: Ethics in Scientific Writing. Section 1 explains the needs and purpose of writing a scientific article in the research and academic field. Section 2, several types of scientific writing are discussed and presented while Section 3 explains on the attributes of a good content outline used in the scientific manuscript. Section 4 emphasizes on the usage of proper English language in term of nouns and punctuations. Section 5 reflects in details the common ethical issue in writing research articles. Lastly, proper selection of journal and submission process for the journal is highlighted in Section 6.